Re-evaluating the Authenticity of Hadith on the Shariah Ruling of Female Circumcision in Malaysia - Ithnin, Norazam Khair Mohd (Al-Bayān, 2023)
The practice of female circumcision in Malaysia has been heavily criticized for being like the practice of Female Genital Mutilation (FGM) in Africa. This criticism started from the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW) in 2018, organized by the United Nations Human Rights (UNHR), which called on Malaysia to stop the practice of female circumcision. Among the accusations made were that the practice of female circumcision was merely a tradition and not a religious requirement. In addition, they denied the authority of the hadith used as evidence for the legitimization of female circumcision, claiming that they were weak and lacked authority. Therefore, this study aims to reassess and re-evaluate the validity and authority of the hadith used as evidence for the legitimization of female circumcision. This study uses a qualitative method, employing historical-textual analysis, to analyze the opinions of hadith scholars regarding the sanad (Transmission) and matan (Text) of the hadith. The results of this study found that the hadith regarding female circumcision has various pathways that can support each other and can be upgraded to hasan li ghayrihi. In conclusion, this study found that the hadith used as evidence for the legitimization of female circumcision is authoritative, thereby affirming that this practice is part of Islamic law.